Characteristic And Potential Of Perlis Carbonate Rock In The Downstream Industries - Abd Rahim, Muhammad Anwar (Universiti Sains Malaysia, 2022)
Carbonate rocks from Chuping, Perlis, Malaysia was analysed for their prospective application in the downstream industries such as glass, cement, agriculture, construction, and steelmaking. The composition chemical examinations of carbonate rocks reveal that greater than 90 percent of the rocks' composition is calcium oxide (CaO), indicating that the composition carbonate in rock is high. The sample are also being studied with hydrochloric acid (HCL) to detect the surface reactivity. The point load test is also performed to measure the sample's strength. To determine the influence of the calcination procedure on the characteristics of sample, the sample was calcined. The investigations of X-ray diffraction and Fourier-transform infrared spectra revealed that heat treatment of sample significantly contributed to the elimination of the CaCO3 phase, resulting in the formation of the CaO form. The scanning electron microscopy microphotographs of sample revealed that the calcination process drastically altered the morphological features, resulting in the production of a highly porous surface with minute spherical particles. The decrepitating and reactivity tests revealed the industrial grade of the rock. Based on its favourable physical qualities, the results indicated that Perlis rock has significant potential for use in a variety of downstream sectors.